Analysis of Physical Fitness of Elementary School Students in Tempe and Sajoanging Districts, Wajo Regency During the Covid-19 Pandemic - Jamaluddin, Jamaluddin; Jamaluddin, Fathurrahman; Hasan, Muhammad Said; Muslim, Muslim (Poltekita : Jurnal Ilmu Kesehatan, 2023)
This study presents a comparative analysis of the physical fitness levels of elementary school students aged 10-12 in the Tempe and Sajoanging Districts of Wajo Regency. Utilizing a descriptive research approach, the research employed the Indonesian Physical Fitness Test (TKJI) instrument from the Ministry of National Education for data collection. The sample comprised 120 students selected through cluster sampling techniques. The data analysis involved t-test analysis, preceded by normality and homogeneity tests. The results indicated that the majority of students at SDN Kec. In Tempe exhibited physical fitness levels in the moderate and poor categories, with percentages of 6.6%, 75.0%, and 18.4%, respectively, for moderate, poor, and very poor categories. Conversely, at SDN Kec. In Sajoanging, the majority fell into the moderate (15.0%), poor (80.0%), and very poor (5.0%) categories. Overall, the general physical fitness level of students in both sub-districts was deemed poor. Comparing these findings with prior research by Ashadi Faqih and Sasminta Christina Yuli Hartati (2017), which focused on South Gugus Elementary School in Tuban Regency, it is evident that the physical fitness levels of students in Tempe and Sajoanging Districts are notably lower. Furthermore, the statistical analysis revealed a significant difference in the physical fitness levels between the two districts. Notably, students at SDN Sajoanging District demonstrated better physical fitness levels than their counterparts at SDN Tempe District. Specifically, a higher percentage of students in Sajoanging District fell into the poor category, while Tempe District had a greater proportion in the very poor category. In conclusion, the research underscores the importance of addressing the poor physical fitness levels among elementary school students in Tempe and Sajoanging Districts. The findings provide valuable insights for educational policymakers and practitioners to develop targeted interventions aimed at improving the overall health and well-being of students in the region.